Politeness Strategy of Request in Traditional Market - Agnes Imam Pratiwi; Juli Rachmadhani Hasibuan (Universitas Negeri Medan, 2021)
This study aimed at analyzing the kind politeness strategy in request which represented in Traditional Market. The descriptive qualitative method used to gain the findings of the data itself. From the findings, 11 requests from 7 speakers have been analyzed. And from those, 21 requests filtered through transcribing the event. Of all 21 requests, it was found that there were 2 politeness strategies used, they were Bald-On record 32 (32%), and Positive Politeness 11 (1,21%) and offRecord16 (5,6%). Later on, the positive politeness was the dominant type of politeness since the traditional market was a full of bargaining, the using of positive politenesswould be found in many ways. The instrument of this study was recording the eventand transcribing them into list. And from that list, the categorization would be easy to extract the data. Thus the writer found that positive politeness that used also similar to another local traditional market.